Effects of S-propargyl-cysteine (SPRC) in caerulein-induced acute pancreatitis in mice. - Jenab N Sidhapuriwala (PLoS ONE, 2012)
Hydrogen sulfide (H(2)S), a novel gaseous messenger, is synthesized endogenously from L-cysteine by two pyridoxal-5'-phosphate-dependent enzymes, cystathionine β-synthase (CBS) and cystathionine γ-lyase (CSE). S-propargyl-cysteine (SPRC) is a slow H(2)S releasing drug that provides cysteine, a substrate of CSE. The present study was aimed to investigate the effects of SPRC in an in vivo model of acute pancreatitis (AP) in mice. AP was induced in mice by hourly caerulein injections (50 µg/kg) for 10 hours. Mice were treated with SPRC (10 mg/kg) or vehicle (distilled water). SPRC was administered either 12 h before or 3 h before the induction of pancreatitis. Mice were sacrificed 1 h after the last caerulein injection. Blood, pancreas and lung tissues were collected and processed to measure the plasma amylase, plasma H(2)S, myeloperoxidase (MPO) activities and cytokine levels in pancreas and lung. The results revealed that significant reduction of inflammation, both in pancreas and lung was associated with SPRC given 3 h prior to the induction of AP. Furthermore, the beneficial effects of SPRC were associated with reduction of pancreatic and pulmonary pro-inflammatory cytokines and increase of anti-inflammatory cytokine. SPRC administered 12 h before AP induction did not cause significant improvement in pancreatic and lung inflammation. Plasma H(2)S concentration showed significant difference in H(2)S levels between control, vehicle and SPRC (administered 3 h before AP) treatment groups. In conclusion, these data provide evidence for protective effects of SPRC in AP possibly by virtue of its slow release of endogenous H(2)S.